PENGEMBANGAN SDM MELALUI PENINGKATAN KOMPETENSI DIKLAT TERHADAP PEGAWAI BAGIAN UMUM DAN KEPEGAWAIAN DI KANTOR OTORITAS BANDARUDARA WILAYAH I KELAS UTAMA - Inezzia Elri Santi; Sri Yanthy Yosepha (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
This research is based on the importance of developing human resources through increasingcompetence in order torealize competent Civil Servants in the administration of governmentin the field of personnel administration. This is intended to study and analyze the developmentof human resources through increasing competence in the Agency for Personnel and HumanResources Development at Kantor Otoritas Bandar Udara Wilayah I Kelas Utama. Thisresearch is descriptive, using an inductive qualitative approach, with data collectiontechniques through interviews, observation, and documentation. In this study, it was revealedthat the Implementation of Human Resource Development Through CompetencyImprovement was classified as not effective, caused by factors namely Knowledge, Skills andAttitudes/Behavior of Civil Servants. The need for commitment and a strong desire for thePersonnel and Human Resources Development Agency of Kantor Otoritas Bandar UdaraWilayah I Kelas Utama to pay attention to human resource development through increasingthe competence of Civil Servants, to meet the quality standards of civil servants who haveprofessional knowledge, skills and attitudes/behaviors